Model Strategis Pengembangan Ekowisata Berkelanjutan: Analisis Swot di Destinasi Taman Eden 100 - Fairy Sinaga; Rusmauli Simbolon; Apriliana Lase; Tio R.J Nadeak; Liyus Waruwu (Yayasan Literasi Sains Indonesia, 2025)
The development of the Taman Eden 100 tourist attraction faces various challenges, such as a lack of marketing strategies, limited supporting facilities, and minimal community involvement in tourism management. This study aims to formulate a strategy for developing the Taman Eden 100 ecotourism destination in Lumban Julu District, Toba Regency. The research method uses a descriptive qualitative approach with observation, interview, and documentation techniques. The results of the study indicate that the development of the Taman Eden 100 ecotourism requires an integrated strategy that optimizes ecological strengths and educational values, improves internal weaknesses, takes advantage of ecotourism trend opportunities, and anticipates external threats. Through the integration of the results of the SWOT analysis, a development strategy is formulated that includes the development of interpretation routes and educational tour packages, improvements in accessibility and environmentally friendly facilities, strengthening digital promotions, conservation-based product differentiation, and the establishment of a multi-stakeholder cooperation forum. This approach is in line with the concept of Sustainable Community-Based Tourism (S-CBT) which emphasizes inclusivity and community empowerment, as well as the principles of Tourism 4.0 which utilizes digital technology to support destination sustainability. Thus, this study provides a theoretical contribution to the literature on community-based ecotourism and a practical contribution in the form of a strategic roadmap for the management of Taman Eden 100 to realize a competitive, sustainable, and educational destination. Expectations for future research: More in-depth research is needed on the role of local communities in implementing the designed ecotourism strategy, including the social, cultural, and economic factors that influence the extent of their involvement.